2009
DOI: 10.1253/circj.cj-09-0320
|View full text |Cite
|
Sign up to set email alerts
|

Pro12Ala Polymorphism of the Peroxisome ProliferatorActivated Receptor-.GAMMA. Gene is Associated With Metabolic Syndrome and Surrogate Measures of Insulin Resistance in Healthy Men Interaction With Smoking Status

Abstract: Background:The Pro12Ala polymorphism (rs1801282), a nonsynonymous substitution of peroxisome proliferator-activated receptor-γ (PPARG), has been robustly associated with type 2 diabetes. However, its role in metabolic syndrome (MetS) remains poorly understood. The associations among rs1801282, MetS and surrogate measures of insulin resistance (IR) were investigated in the present study. Methods and Results:A cross-sectional population-based survey of 572 unrelated healthy male Argentinian blood donors with nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 55 publications
(70 reference statements)
2
27
0
1
Order By: Relevance
“…Some de scribe that the presence of polymorphisms confers a protective effect with respective do type 2 diabetes risk (12), whereas others indicate that it is associated with increased susceptibility to the disease (8,13). There are also studies in which no association was found be tween this variant and the frequency of type 2 diabetes (14 16).…”
Section: Introductionmentioning
confidence: 99%
“…Some de scribe that the presence of polymorphisms confers a protective effect with respective do type 2 diabetes risk (12), whereas others indicate that it is associated with increased susceptibility to the disease (8,13). There are also studies in which no association was found be tween this variant and the frequency of type 2 diabetes (14 16).…”
Section: Introductionmentioning
confidence: 99%
“…Namely, the type 2 diabetes risk allele of PPARG rs1801282 previously found to associate with insulin resistance [11,12] and the ADCY5 variant previously found to associate with birthweight and fasting glucose apart from HOMA-B [13,14]. The major allele of G6PC2 rs560887 was associated with decreased HOMA-B as well as increased insulinogenic index.…”
Section: Discussionmentioning
confidence: 94%
“…These results suggested that polymorphisms at the rs3856806 locus were associated with the occurrence of MS in Kazakhs, and the C allele was a risk factor for MS. In contrast, Tellechea et al (2009) studied 572 Argentinean people and found that polymorphisms at the rs1801282 locus were associated with the incidence of MS. They also found that smoking increased the likelihood of developing MS. Huguenin and Rosa (2010) conducted a meta-analysis and found that rs1801282 polymorphisms were associated with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic susceptibility is also a major cause of MS. Recent reports have shown a correlation between polymorphisms in peroxisome proliferator activated receptor γ (PPARγ) and components of MS, such as hypertension, diabetes and obesity; however, the conclusions from these studies are inconsistent (Tellechea et al, 2009;Huguenin and Rosa, 2010;Bego et al, 2011). Whether polymorphisms at multiple loci of the PPARγ gene are related to the occurrence of MS in Uyghurs and Kazakhs remains unclear.…”
Section: Introductionmentioning
confidence: 99%